Community Empowerment of Bangunrejo Village in Waste Management: Impact Analysis and Implementation - Akbar Najih Amrullah; Sri Sumarti; Isna Akmilna Latifa; Aang Asari (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Waste that is not properly processed can cause environmental pollution. In Bangunrejo Village, problems were found in waste management. The emergence of problems in waste management is caused by various factors such as lack of public awareness and supporting facilities and infrastructure. The accumulation of waste in Bangunrejo Village has a significant negative impact on the environment, including soil and water pollution, as well as health problems for local residents. This study aims to analyze the factors causing waste accumulation, negative impacts on the environment, and handling efforts that can be carried out in Bangunrejo Village. The results of the study indicate that active participation between village communities and support from the village government are the keys to success in creating a clean and healthy environment in Bangunrejo Village.